In-Depth Genomic Characterization of a Meropenem-nonsusceptible Pseudomonas otitidis Strain Contaminating Chicken Carcass - Regina Vieira, Tatiana; Enck Sambrano, Gustavo; Michelle Vieira da Silva, Núbia; Carvalho Vasconcelos, Priscylla; Cavinatto de Oliveira, Esther Ferraza; Bruno de Oliveira, Celso José; Cibulski, Samuel Paulo; Cardoso, Marisa (Acta Scientiae Veterinariae, 2020)
Background: The indiscriminate use of antibiotics in food-animal production has a major impact on public health, particularly in terms of contributing to the emergence and dissemination of antimicrobial resistant bacteria in the food-animal production chain. Although Pseudomonas species are recognized as important spoilage organisms in foodstuff, they are also known as opportunistic pathogens associated with hospital-acquired infections. Furthermore, Pseudomonas can play a role as potential reservoirs of antimicrobial resistance genes, which may be horizontally transferred to other bacteria. Considering that cephalosporins (3rd and higher generations) and carbapenems are critically important beta-lactam antimicrobials in human medicine, this study reports the occurrence and genomic characterization of a meropenem-nonsusceptible Pseudomonas otitidis strain recovered from a chicken carcass in Brazil. Materials, Methods & Results: During the years 2018-2019, 72 frozen chicken carcasses were purchased on the retail market from different regions in Brazil. Aliquots from individual carcass rinses were screened for Extended Spectrum Beta-lactamase (ESBL)-producing bacteria in MacConkey agar supplemented with 1mg.L-1 cefotaxime. Phenotypically resistant isolates were further tested for resistance to other antimicrobials and confirmed as ESBL-producers by means of disk-diffusion method using Müller-Hinton agar. Only one meropenen-nonsusceptible isolate was detected and submitted to whole genome sequencing (WGS) in Illumina Miseq. The strain was identified as Pseudomonas otitidis by local alignment of the 16S rRNA sequence using BLASTn and confirmed by Average Nucleotide Identity (ANI) analysis using JspeciesWS database. Genes encoding for antimicrobial resistance were detected by means of Resfinder and Comprehensive Antibiotic Resistance Database (CARD) databases. The phenotypic non-susceptibility to meropenen was attributed to the gene blaPOM-1. A total of 192 different genes encoding for quorum sensing system, antiphagocytosis, iron uptake, efflux pump, endotoxin and toxin, adherence, and secretion systems were detected by means of Virulence Factor Database (VFDB). Pseudomonas otitidis-pan genome was built using Roary-rapid large-scale prokaryote pan genome analysis using the present strain (K_25) and other two P. otitidis genomes (PAM-1, DSM 17224) publicly available at the NCBI. The core genome analysis of the two human strains resulted in similar percentages. Discussion: Carbapenems are critically important drugs for human health and bacterial strains resistant to these antimicrobials pose a public health problem. The blaPOM-1 gene harbored by the Pseudomonas otitidis K_25 strain encodes a metallo-beta-lactamase (MBL) conferring resistance to carbapenems. Pseudomonas otitidis was the first confirmed pathogenic Pseudomonas species expressing MBL constitutively in the absence of inducible beta-lactamase genes. Furthermore, the several virulence genes associated with the capacity of the P. otitidis K_25 to colonize, evade the immune system and cause lesions in the human host confirm this strain as a potential opportunistic pathogen contaminating foodstuff. These reinforce the need to address antimicrobial resistance in a One Health perspective, in which resistant bacteria and resistance determinants circulate among environment, animals and humans.